Utilization of Bar Soap (Sabbath) Becomes Liquid Hand Soap to Prevent the Spread of Covid-19 (Community Service in Singocandi Village, City District, Kudus Regency) - Munawar Kholil (Universitas Sebelas Maret, 2020)
The problems of the people of Singocandi Village RT 001 RW 002 related to the habit of using bar soap as hand washing soap are increasing. Bar soap is recommended to only be used by one person. The use of bar soap interchangeably is not recommended because it is not hygienic and is thought to be able to transmit disease. Moreover, it is used as hand soap by the whole family. The purpose of the activity of using bar soap into liquid hand washing soap is a form of the Covid-19 Community Service Program which is carried out in Singocandi Village to maintain cleanliness and body health and increase the creativity of local residents. Processing of bar soap, if developed, is expected to increase the habit of a clean and healthy lifestyle and increase income in Singocandi Village. The method of implementation carried out in this activity is: (1) delivery of material on how to make liquid hand soap from bar soap. (2) practice with the children of RT 001 / RW 002.The result is increased knowledge, innovation and creativity, the creation of liquid soap products, and habits of a clean and healthy lifestyle